2012
DOI: 10.1111/j.1442-2042.2012.03000.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of bladder overactivity and oxidative stress by the phytotherapeutic agent, Eviprostat, in a rat model of atherosclerosis‐induced chronic bladder ischemia

Abstract: Abbreviations & Acronyms 8-OHdG = 8-hydroxy-2′-deoxyguanosine AI = arterial injury AI/Evi = arterial injury/Eviprostat group AI/veh = arterial injury/vehicle group BOO = bladder outlet obstruction BPH = benign prostatic hyperplasia DO = detrusor overactivity IL = interleukin LUTS = lower urinary tract symptoms MDA = malondialdehyde ROS = reactive oxygen species TNF = tumor necrosis factor Objectives: To clarify the mechanism by which chronic bladder ischemia causes bladder functional changes, and to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Excess production of ROS might be involved in the development of overactive bladder, including ischemia/reperfusion and aging . Protamine sulfate is known to affect the bladder permeability barrier and to damage the urothelial cell surface, which increases lipid peroxidation from free radicals and results in oxidative injury .…”
Section: Discussionmentioning
confidence: 99%
“…Excess production of ROS might be involved in the development of overactive bladder, including ischemia/reperfusion and aging . Protamine sulfate is known to affect the bladder permeability barrier and to damage the urothelial cell surface, which increases lipid peroxidation from free radicals and results in oxidative injury .…”
Section: Discussionmentioning
confidence: 99%
“…Eviprostat [61] , Coenzyme Q10 [62,63] and melatonin [64] were found to reverse several bladder functional injuries caused by bladder ischemia, contributing to strengthen the oxidative/pro-inflammatory theory behind a decreased bladder blood flow. Finally, stem cell therapy is also making its entry in the field of the ischemia-induced bladder dysfunction.…”
Section: Treatment Of Ischemic Oabmentioning
confidence: 90%
“…Several studies suggested the effective role of anti-oxidant agents in the protectiveness and reversal of bladder ischemia lesions [61][62][63][64] . Eviprostat [61] , Coenzyme Q10 [62,63] and melatonin [64] were found to reverse several bladder functional injuries caused by bladder ischemia, contributing to strengthen the oxidative/pro-inflammatory theory behind a decreased bladder blood flow.…”
Section: Treatment Of Ischemic Oabmentioning
confidence: 99%
“…The rats were raised for 21 consecutive days for successful establishment of the models (Lin et al, 2012;Matsui et al, 2012).…”
Section: Establishment Of Atherosclerosis Modelsmentioning
confidence: 99%